Effectiveness of different types of direct corrective feedback on correct use of English articles among the Iranian EFL students - Soori, Afshin; Shokrpour, Nasrin (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
One major issue that has obsessed the scholars' minds is how to provide the students with fruitful feedback that will have a positive effect on students' writing processes, and so best contribute to improve overall, long-term quality of their writing. It remains no easy answer to the question of what kind of feedback the teacher should give the students. However, teachers should focus on implementing types of feedback that make students maximize utilizing the prior feedback on subsequent writing occasions. To this end, we seek to fill a gap in the research by investigating the effectiveness of different types of direct corrective feedback on the correct use of English articles among the Iranian EFL students. The knowledge in this area will hopefully help the teachers to provide the EFL students with the most fruitful feedback and help them to notice their errors and internalize a system to correct them. Apart from a rather limited research base, and some conflicting findings, scarcely any attention has been given to an investigation of the relative merits of different types of direct corrective feedback on linguistic errors. Firm conclusions will only become available if further research, incorporating different types of corrective feedback within a design of a single study, is carried out.